Voxel-Wise Meta-Analysis of Gray Matter Changes in Amyotrophic Lateral Sclerosis - Shen, Dongchao; Cui, Liying; Fang, Jia; Cui, Bo; Li, Dawei; Tai, Hongfei (Frontiers in Aging Neuroscience, 2016)
Background: Increasing neuroimaging studies have revealed grey matter (GM) anomalies of several brain regions by voxel-based morphometry (VBM) studies in patients with amyotrophic lateral sclerosis (ALS). A voxel-wise meta-analysis was conducted to integrate the reported studies to determine the consistent GM alterations in ALS based on VBM methods. Methods: Ovid Medline, Pubmed, Emabase and BrainMap database were searched for relevant studies. Data were extracted by two independent researchers. Voxel-wise meta-analysis was performed using the effect-size signed differential mapping (ES-SDM) software. Results: Twenty-nine VBM studies comprising 638 subjects with ALS and 622 healthy controls (HCs) met inclusion criteria. The global GM volumes of ALS patients were significantly decreased compared with those of HCs. GM reductions in patients were mainly located in the right precentral gyrus, the left Rolandic operculum, the left lenticular nucleus and the right anterior cingulate/paracingulate gyri. The right precentral gyrus and the left inferior frontal gyrus might be potential anatomical biomarkers to evaluate the severity of the disease, and longer disease duration was associated with more GM atrophy in the left frontal aslant tract and the right precentral gyrus in ALS patients. Conclusion: The results support that ALS is a complex degenerative disease involving multisystems besides the motor system. The mechanism of asymmetric atrophy of the motor cortex and the implication of Rolandic operculum involvement in ALS need to be further elucidated in future studies.